Princípios da educação escolar indígena e práticas pedagógicas da Escola da Aldeia Manga / Oiapoque-AP - (:unkn) unknown (UNIFAP - Universidade Federal do Amapá, 2025)
This research presents the concepts underlying the principles of Indigenous schools, taking the National Curriculum Framework for Indigenous Schools (RCNEI) as its theoretical foundation, along with other authors who study contemporary Indigenous education in Brazil. The study analyzes the pedagogical practices of Indigenous teachers at the E.I.E. Jorge Iaparrá School, located in the Manga village, and discusses the ways in which they work with their classes. It also seeks to develop a reflection in light of the legislation and other guiding documents that establish the foundations of Indigenous school education. The research is guided by the following question: how do the pedagogical practices developed by teachers working in the early years (3rd to 5th grades) of Elementary Education at E.I.E. Jorge Iaparrá reflect the principles of interculturality, bilingualism, community-based, specific, and differentiated education—core concepts of Indigenous school education as advocated by the Indigenous movement and enshrined in current Brazilian legislation? The general objective is to analyze the pedagogical practices of teachers working from the 3rd to the 5th grade at E.I.E. Jorge Iaparrá, relating these practices to the pedagogical principles that characterize Indigenous schooling. The research follows a qualitative approach, using a case study design, with participant observation and semi-structured interviews as data collection techniques. The results show that the pedagogical principles are present in the practices of the teachers at E.I.E. Jorge Iaparrá, mainly through orality, and that cultural knowledge interacts with these principles during class activities and the cultural week.
Keywords: Comunidade indígena - Macapá (AP); Práticas pedagógicas; Interculturalidade e bilinguismo - Ensino fundamental; Comunidade indígena - Macapá (AP); CNPQ::CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO; ODS 4 – Educação de qualidade; ODS 10 – Redução das desigualdades; ODS 16 – Paz, justiça e instituições eficazes